Going Green, but Staying in the Black: How Framing Impacts the Agreement With Messages on the Economic Consequences of Environmental Policies - Bertolotti, Mauro; Catellani, Patrizia (Frontiers in Psychology, 2021)
Past research suggests that although citizens are generally favorable to pro-environmental policies, their negative economic impact can be a relevant source of concern. In two studies, we investigated the agreement with messages highlighting the positive vs negative economic impact of a pro-environmental policy (the creation of a protected natural reserve in a lakeside area), as a function of the framing of the policy itself in terms of local relevance (Study 1) and environmental impact (Study 2). In Study 1, participants (N = 514) were citizens of different Italian regions. Results showed that reference to the local (vs global) relevance of the proposed policy increased the tendency to agree with loss-framed (vs gain-framed) messages on the economic impact of the policy. In Study 2, participants (N = 500) were a sample of actual lakeside residents from the Garda Lake area in Italy. Results showed that reading messages promoting the policy through stressing the negative consequences of not implementing it (vs the positive consequences of implementing it) increased the tendency to agree with a subsequent loss-framed (vs gain-framed) message on the economic impact of the policy. This effect was more evident among participants with stronger place identity. Discussion focuses on the relevance of framing and matching effects in devising persuasive messages on the environmental and economic impact of pro-environmental policies.